United States. Army. Office of the Chief of Engineers letterpress book - United States. Army. Office of the Chief of Engineers; Frost, Edward (Engineer)
Letterpress book containing copies of letters (1862 May 9-1865 June 8) sent by Edward Frost and other engineers, Office of Engineers, responsible for defenses of Washington, D.C., south of the Potomac River.
Collection material in English.
Keywords: Fortification -- Washington (D.C.); Potomac River Valley -- History -- Civil War, 1861-1865.; United States -- History -- Civil War, 1861-1865.; Washington (D.C.) -- History -- Civil War, 1861-1865.